Assistive technologies for aged care: Comparative literature survey on the effectiveness of theories for supportive and empowering technologies. Issue 2 (3rd April 2018) - Vichitvanichphong, Suchada; Talaei-Khoei, Amir; Kerr, Don; Ghapanchi, Amir Hossein
Abstract : Purpose: One may categorize assistive technologies for aged care into two types, namely, supportive (helping the elderly with their everyday activities) and empowering (obtaining physical or educational training to help seniors to maintain their capabilities). This paper looks at the impact of this perspective in the adoption of technologies that are used to aid already declined functions in comparison with technologies that are used to empower an elderly person's capabilities. The purpose of this paper is to extract the factors that influence adoption of assistive technologies among seniors and the theories used in this context. Design/methodology/approach: A systematic literature review was conducted on relevant peer reviewed papers. A preliminary exploratory search was conducted to identify keywords and online databases for the search. A total of 104 papers published since 2000 were analyzed after title, abstract and full text filtering. Findings: The study summarizes and categorizes the factors impacting the adoption of assistive technologies among seniors. The paper analyses the theoretical support utilized by literature and maps the empirical evidence for supportive and empowering technologies. Research limitations/implications: This research like any other literature review is limited to the search keys. However, the keys have brought to this work from a preliminary search. Practical implications: The work informs nursing professionals on the process to adopt technologies among seniors. The paper also helps technology developers to design technological products that are easier to adopt for older adults. Originality/value: It was found that existing adoption theories are able to handle supportive technology adoption mainly because of the direct link between usage and improved functionalities. However due to the indirect effect of empowering technologies, elderlies lag in benefit realization for empowering technologies. This opens avenues of research and requires future work and utilization of new theoretical approaches in this area. The paper indicates propositions, claims and suggested questions for future research in both supportive and empowering technologies.